PENERAPAN SERTIFIKASI HALAL MUI DAN EDUKASI JAMINAN PRODUK HALAL PADA BUBUK KOPI ARABICA DI POKMAS WALIDA DESA TLOGOSARI KECAMATAN SUMBERMALANG KABUPATEN SITUBONDO - Anam, Moh Khoirul; Saifuddin; Wulandari, Ana Sri (Penerbit Lafadz Jaya, 2023)
The application of halal certification has an important role in a product because it shows that the product does not contain ingredients prohibited by Islamic Sharia and has been processed in a way that complies with Islamic Shari'a. Therefore, the Indonesian government is also trying to develop the halal food and beverage industry in the country to encourage the growth of the halal industry. Law Number 33 of 2014 concerning Halal Product Assurance was created to encourage the acceleration of the implementation of halal standards, one of which is halal certification. This law, in Article 4, stipulates that products must have halal certification. One of the objectives of this research is how the application of halal certification and education about halal product assurance is applied to the arabica coffee powder business in Pokmas Walida Situbondo. This study uses a type of qualitative research method, using descriptive analytical techniques to see in depth the application of halal certification and education on halal product assurance on Arabica coffee powder in Pokmas Walida, Sumbermalang District, Situbondo Regency.